Growth Kinetics Modelling of Tributytin-Resistant Klebsiella SP. FIRD 2 In Cadmium Media - Abdussamad Abubakar; Nazeef Idris Usman; Hadiza Ibrahim; Abdullahi Muhammad; Usman Sunusi; Ferdaus Mohamat-yusuff; Salihu Ibrahim (UMYU Journal of Microbiology Research)
Tributyltin (TBT) has been generally used as component of antifouling biocide in boat and ship paints to prevent the attachment of marine organism on the hull surface. TBT has been classified to be a very toxic compound, and poses significant danger to a broad diversity of organisms in the polluted environments due to the high concentrations. The growth kinetic of TBT-Resistant Bacterium containing cadmium was studied. In this study various cadmium concentrations ranging from 1 to 100 mg/L were used. Seven kinetic models (Haldane, Teissier, Monod, Yano, Luong, Aiba and Webb) were investigatedand the accuracy of the fitted model were evaluated using statistical analysis such as coefficient of determination, adjusted coefficient of determination (R2) and root mean square (RMSE). Luong model were fitted to the experimental growth kinetics data and gave a very good fit. The calculated value for the Luong constants such as maximal growth rate, half saturation constant and half inhibition constant rate symbolized by umax, ks, and ki, were 0.03405 hr-1, 0.3 mg/L and 0 mg/L, respectively. Luong model also predicted the significant substrate concentration (Sm) value, at which specific substrate degradation rate falls to zero (98.93 mg/L). This is the first report of growth kinetics of TBT-Resistant bacterium by Klebsiella sp. FIRD 2 Containing Cadmium